Mapping of the ligand-binding site on the b′ domain of human PDI: interaction with peptide ligands and the x-linker region - Lee J. Byrne; Ateesh Sidhu; A. Katrine Wallis; Lloyd W. Ruddock; Robert B. Freedman; Mark J. Howard; Richard A. Williamson (2009)
PDI (protein disulfide-isomerase) catalyses the formation of native disulfide bonds of secretory proteins in the endoplasmic reticulum. PDI consists of four thioredoxin-like domains, of which two contain redox-active catalytic sites (a and a'), and two do not (b and b'). The b' domain is primarily responsible for substrate binding, although the nature and specificity of the substrate-binding site is still poorly understood. In the present study, we show that the b' domain of human PDI is in conformational exchange, but that its structure is stabilized by the addition of peptide ligands or by binding the x-linker region. The location of the ligand-binding site in b' was mapped by NMR chemical shift perturbation and found to consist primarily of residues from the core beta-sheet and alpha-helices 1 and 3. This site is where the x-linker region binds in the X-ray structure of b'x and we show that peptide ligands can compete with x binding at this site. The finding that x binds in the principal ligand-binding site of b' further supports the hypothesis that x functions to gate access to this site and so modulates PDI activity.